Mental health status among Chinese healthcare-associated infection control professionals during the outbreak of coronavirus disease 2019: A national cross-sectional survey. Issue 5 (5th February 2021) - Zhang, Ying; Tian, Lingyun; Li, Wan; Wen, Ximao; Wu, Hongman; Gong, Ruie; Zeng, Lanman; Zhou, Feng; Liu, Zhenru; Tang, Ziyuan; Wu, Anhua; Huang, Xun
Abstract : Abstract: Recently, the coronavirus disease 2019 (COVID-19) epidemic has greatly threatened global public health. The responsibility of healthcare-associated infection control professionals (ICPs) is to prevent and control the nosocomial infections. The mental health status of ICPs deserves more attention, however, the correlational research is still lacking. This study aims to investigate the incidence and risk factors of mental health status among ICPs in China during the outbreak of COVID-19. A national cross-sectional survey was performed. The online questionnaire was completed by 9228 ICPs from 3776 hospitals throughout China. Data collection tools were used, including demographics data questionnaire, the Chinese version of the 12-item general health questionnaire (GHQ-12) and the Chinese version of the psychological capital questionnaire (PCQ) for medical staff. Univariate and multivariable analyses were conducted. The total score of mental health of Chinese ICPs was 3.45 ± 2.57. 5608 (60.77%) ICPs might have mental health problems. The psychological capital was in the upper-middle level with an average score of 3.72 ± 0.38. An increased mental health problem risk was associated with the greater self-efficacy and working in the public hospital; a significantly lower risk was obtained by working in the second-class hospital rather than in the third-class hospitals. Besides, mental health problem risk of ICPs working in hospitals of the western economic region or northeast economic region was more significant than that in hospitals of the central economic region. However, a lower risk was caused by the unmarried than married, and working years in department ⩽1 year contributed to the lower risk than that >20 years. Moreover, fewer working hours per week, higher values of hope, and optimism each were contributed to a lower risk. Chinese healthcare-associated ICPs were under different levels of mental health problems in fighting against COVID-19. More importantly, we should actively deal with the mental health problem of ICPs and help them get rid of psychological disorders.